Handbook of radiation effects - Holmes-Siedle, Andrew (Oxford University Press, 2002)
This revised second edition of a popular handbook for engineers fills a gap in the fields of high-energy radiation environments, electronic device physics and materials. It is a straightforward account of the problems which arise when high-energy radiation bombards matter and of engineering methods for solving those problems. X-ray, electron and the'hadron's' in CERN's new collider environments and several more are described. The impact of these environments on microelectronics in computing, data processing and communication is the core of this book. A large amount of technical data, needed to make predictions on the spot, is presented, with literature references needed for further research and also a compendium of websites which have been tested and used by the authors